2014
DOI: 10.1186/s12989-014-0045-5
|View full text |Cite
|
Sign up to set email alerts
|

A controlled trial of acute effects of human exposure to traffic particles on pulmonary oxidative stress and heart rate variability

Abstract: BackgroundFor many individuals, daily commuting activities on roadways account for a substantial proportion of total exposure, as well as peak-level exposures, to traffic-related air pollutants (TRAPS) including ultrafine particles, but the health impacts of these exposures are not well-understood. We sought to determine if exposure to TRAPs particles during commuting causes acute oxidative stress in the respiratory tract or changes in heart rate variability (HRV), a measure of autonomic activity.MethodsWe con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 50 publications
0
36
1
1
Order By: Relevance
“…Sample preparation EBC samples collected for a previous study 53 were utilized. The details of the sample collection procedure have been previously described, but briefly, 1-2 mL of EBC was collected during 20 min of tidal breathing from each of seven adult subjects using an EcoScreen device (Jaeger, Wurzburg, Germany), which condensed the exhaled breath at − 20°C.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sample preparation EBC samples collected for a previous study 53 were utilized. The details of the sample collection procedure have been previously described, but briefly, 1-2 mL of EBC was collected during 20 min of tidal breathing from each of seven adult subjects using an EcoScreen device (Jaeger, Wurzburg, Germany), which condensed the exhaled breath at − 20°C.…”
Section: Methodsmentioning
confidence: 99%
“…All surfaces were triple-rinsed with nitrite-free water prior to contacting the EBC, and the samples were frozen at − 80°C for later analysis. In the previous study, nitrite concentrations were measured using selective catalytic reduction and chemiluminescence detection (NOA 280i, GE Analytics, Boulder, CO, USA) 53 . All solutions were prepared with distilled water.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the authors noted that these study were not double blinded, and so the findings may be biased by subjects’ awareness of whether they were wearing a respirator or not. Another study reported that markers of oxidative stress (nitrite and nitrite + nitrate) in exhaled breath condensate were increased immediately after 1.5-h car rides during which subjects breathed unfiltered vehicle cabin air, but not after rides during which subjects breathed HEPA-filtered air via a powered air purifying respirator [41]. Unfortunately, under most daily life scenarios, wearing face masks is not a long-term practical strategy; however, it may be useful for short periods during extreme exposures (e.g., high-risk individuals during travel to polluted regions, occupational exposures, activities near hot spots such as roadways).…”
Section: Interventions To Reduce Air Pollution Exposures At a Personamentioning
confidence: 99%
“…The extended duration and heavy breathing associated with manual labor of certain occupations (e.g. transportation, landscaping, construction) as well as the increased exposure to household air pollution among women, children and the elderly in low- and middle-income countries (who spend more time indoors than male adults) results in a greater burden of exposure and subsequent greater pulmonary disease in these sub-populations 14, 63–65, 229, 234 . The increasing prevalence of acute respiratory diseases has also been linked to climate change and alterations in ground level ozone pollution distribution 228, 229 .…”
Section: 1 Pulmonary Diseasesmentioning
confidence: 99%